Theistic evolution: a contemporary Aristotelian-Thomistic perspective - Tabaczek, Mariusz (Cambridge University Press, 2024)
"For all interested in the dialogue between science and religion, this book offers a fresh, intriguing, and convincing way of reconciling and promoting an inspiring mutual exchange between the well-known Aristotelian-Thomistic tradition of philosophy and theology and the most recent version of biological evolution"--